Geodynamics of the Huacar-Huánuco area - Guadalupe Gómez, Enrique (2004)
The Peru is a country with a complex geodinamyc, for the location of the mountain ranges Westerner and oriental, for the diversity of rocks and floors, its multiple climates and ecological floors that accelerate the diverse processes of the external geodinamyc. In Huacar is developed the «Project Pilot of Reforestation with Tare using non Conventional Systems of Watering», it embraces an extension of 120 ha there is, where 120 families intervene in condition of poverty and it carries to an extreme poverty, it leaves of this land it has been affected, especially for slip of floors and erosion for carcavas, that which we will treat study presently.